Long-chain unsaturated free fatty acids reduce the host cell invasion of Listeria monocytogenes outbreak strains - Borreby, Caroline; Hvidtfeldt, Thea Amalie; Jespersen, Magnus Ganer; T. dos Santos, Patricia; Houborg, Sofie Dam; Lillebæk, Eva Maria Sternkopf; Kemp, Michael; Kallipolitis, Birgitte H. (Frontiers in Cellular and Infection Microbiology, 2025)
The Gram-positive bacterium Listeria monocytogenes is a highly adaptable pathogen capable of causing severe foodborne infections, particularly in vulnerable populations. During infection, L. monocytogenes uses a variety of virulence factors to invade and multiply within host cells. The transcriptional regulator PrfA controls the expression of these virulence factors and is essential for the intracellular lifestyle of L. monocytogenes. Long-chain unsaturated free fatty acids (FFAs) have long been recognized for their antimicrobial activity and were recently shown to inhibit PrfA-dependent virulence gene expression in L. monocytogenes. To date, the antimicrobial and anti-virulent activities of FFAs have been primarily studied in laboratory strains. However, to fully evaluate their potential as anti-infective agents, it is essential to assess the effects of long-chain FFAs on clinically relevant isolates, including outbreak strains associated with high-fat food products. Here, we demonstrate that five different clinically relevant L. monocytogenes isolates are sensitive to the antimicrobial activity of long-chain unsaturated FFAs. Furthermore, at subinhibitory concentrations, these FFAs inhibit PrfA-regulated expression of virulence factors across all tested strains and reduce their invasive potential in non-phagocytic cells. These findings underscore the potential of long-chain unsaturated FFAs in developing new preventive strategies against L. monocytogenes strains associated with severe foodborne infections.